ANALISIS HUBUNGAN ANTARA BELANJA MODAL, PENDAPATAN ASLI DAERAH, KEMANDIRIAN DAERAH DAN PERTUMBUHAN EKONOMI DAERAH - Apriana, Dina; Suryanto, Rudy (Universitas Muhammadiyah Yogyakarta, Indonesia, 2010)
Effective fiscal decentralization carried out since 10 years ago, one side gives greater authority in managing the area, but on the other side raises new problems. This is because the level of fiscal readiness of different areas. Increased authority possessed by local governments is expected to increase the independence of the region by maximizing the potentials in order to stimulate economic growth. This study aims to test how much capital expenditure and regional own revenue affect regional sufficiency and economic growth. This research obtained the result that capital expenditures did not significantly affect the regional sufficiency, while regional own revenue has a positive and significant impact on regional sufficiency. This research also obtains the results that capital expenditure, regional own revenue, and regional sufficiency did not significantly influence economic growth.